Employees' perceptions of the effects of retrenchment on job stress and organisational commitment in a mining company - Seteni, Landiswa Pilvia (Vaal University of Technology, 2016)
In the decade before 2005, South African organisations have had to cope with an ever-increasing rate of local and global changes. There have been considerable and ongoing socio-political changes, resulting from new Government regulations. Most organisations have experienced some type of downturn, whether due to external business factors or poor internal performance. A typical response to organisational decline is retrenchment. Retrenchment is attributed to cyclical downturns, market losses or other economic factors, which oblige the employer to reduce the labour force numbers. Though there are so many ways of responding to organisational failure, this study focused only on retrenchment. A number of psychologists and human sciences researchers have studied the results of job loss due to retrenchment. Retrenchment brings loss of skills, loss of morale and commitment, as well as physical and mental health degradation, including stress that results in employees withdrawing physically and emotionally. The main purpose of this study was to outline the employees’ perceptions of the effects of retrenchment on job stress and organisational commitment in a mining company. The research methodology used in this study is a combination of a literature review and an empirical study. The probability sampling technique, which entails using simple random sampling, was used to select the sample of the study. The primary data were collected using a questionnaire. The measuring instrument contained 43 items. The measuring instrument was pilot-tested with 50 respondents three weeks before the main survey; the questionnaire was self-administered to the participants. For the main survey, data from 294 respondents were collected and analysed. Participants in the study involved surface employees, including management, administrators, engineers and artisans. Data were analysed with the Statistical Package for Social Sciences (SPSS) version 23.0. The Cronbach’s alpha coefficients of the various sections of the measuring instrument were computed to establish construct validity. Content validity was ascertained by pre-testing the questionnaire with the employees in the mine in question. Correlations were used to establish convergent validity of the constructs. Convergent validity was assessed to measure the degree of linear association of variables using Pearson’s correlation coefficient. Discriminant validity was achieved by using regression analysis to show items loaded onto different factors in various sections which had more than one factor. Analysis was done using descriptive statistics on the demographic information of respondents. The results were also interpreted through correlation and regression analysis. The results showed that the effects of retrenchment did not have a negative impact on job stress (time stress and anxiety). This may be due to the mine in question planning and consulting with the employees prior to the retrenchment process. The results also showed that job stress (time stress and anxiety) is negatively associated with organisational commitment. Subsequent to these findings, it is recommended that employees (survivors) be updated on their future in the company in question. This could be done through regular workshops and counselling of employees. In order to motivate and engage employees, and thereby contribute to employee commitment, it was also recommended that organisations create open, supportive and fair organisational and team cultures, and ensure jobs are clearly aligned with organisational goals and have appropriate levels of autonomy, support and career development. Given that job satisfaction plays a huge role in organisational commitment, it was further recommended that managers need to actively improve their organisation’s job satisfaction to employees in order to achieve a higher level of organisational commitment. The study concludes by recommending that communication between employees and management should take place on a regular basis which can serve as a fundamental tool to retrenchment in the following manner:  Survivors will feel more committed to the organisation when the basis of retrenchment addresses the circumstances in the external environment, rather than the enrichment of shareholders or top management.  Communicating a clear vision of how retrenchment will benefit stakeholders, increases commitment since survivors can see a clear future for the organisation.  When survivors are treated with dignity and respect, they will feel more committed to the organisation because they feel appreciated.
M. Tech. (Department of Labour Relations Management, Faculty of Management Sciences), Vaal University of Technology.
Keywords: Employees perception; Retrenchment; Job stress; Organisational commitment; Mining company; Anxiety; Dissertations, Academic -- South Africa.; Downsizing of organizations -- South Africa.; Job stress.; Organizational commitment.; Mining corporations.; Miners -- South Africa.